"A Rare Encounter: Pneumoparotid in Clinical Practice" A Case Report - Rimal, Rajesh; Sharma, Umesh Kumar; Thapaliya, Suraj; Shrestha , Manmohan Bir; Limbu, Jayanti; Shrestha, Saujan (Medical Journal of Eastern Nepal, 2024)
Pneumoparotid is a rare condition which is frequently observed in the patients with parotid gland infection or during maneuver leading to increase in intraoral pressure. The common maneuver being performed is puff-cheek technique for diagnostic computed tomography (CT). It is always important to distinguish the etiology of pneumoparotid being pathological or due to maneuver to proceed for further management. Here we present a case of a 56 year old man with suspicion of carcinoma of tongue evaluated by CT using puff cheek technique. On evaluating the images, a finding of bilateral pneumoparotid a case report was made.